THE IMAGE OF CATHERINE BARKLEY - Dilnoza Kholnazarova Rustam qizi; Mukadas Murodova Ikromovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation:The portrayal of women in Ernest Hemingway's fiction has been a topic of much debate. Critics are divided on whether Hemingway presents one-dimensional characters or a more nuanced range of women. Some argue that he falls into stereotypes, categorizing women into “good” or “bad.” Others, however, see a wider spectrum of personalities and motivations. Feminist critics have particularly focused on characters like Catherine Barkley in A Farewell to Arms, with interpretations ranging from her death symbolizing the dominance of men to her representing courage and resilience. Ultimately, the passage leaves it up to the reader to consider the various viewpoints and develop their own analysis of Hemingway’s female characters.